2005
DOI: 10.1164/rccm.200503-504oc
|View full text |Cite
|
Sign up to set email alerts
|

ABCA3 Mutations Associated with Pediatric Interstitial Lung Disease

Abstract: Rationale: ABCA3 is a member of the ATP-binding cassette family of proteins that mediate the translocation of a wide variety of substrates, including lipids, across cellular membranes. Mutations in the gene encoding ABCA3 were recently identified in full-term neonates with fatal surfactant deficiency. Objective: To test the hypothesis that ABCA3 mutations are not always associated with fatal neonatal lung disease but are a cause of pediatric interstitial lung disease. Methods: DNA samples were obtained from 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
246
3
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 285 publications
(263 citation statements)
references
References 24 publications
10
246
3
4
Order By: Relevance
“…These alterations are distinct from those observed in SP-B or ABCA3 deficiency 3,6 and appear specific in both our observations and the literature. 15,28 In SP-C-deficient mice, LBs and extracellular surfactant are similar to controls, 35 suggesting that the human disease is not primarily caused by SP-C haploinsufficiency itself.…”
Section: Polarized Light Microscopycontrasting
confidence: 58%
See 2 more Smart Citations
“…These alterations are distinct from those observed in SP-B or ABCA3 deficiency 3,6 and appear specific in both our observations and the literature. 15,28 In SP-C-deficient mice, LBs and extracellular surfactant are similar to controls, 35 suggesting that the human disease is not primarily caused by SP-C haploinsufficiency itself.…”
Section: Polarized Light Microscopycontrasting
confidence: 58%
“…Prevalence in pDLD series, as in ours, varies from 8 to 17%. 1, 3,6,7,19,26 SP-C mutations have been described in term 15,27 or late preterm infants with severe RDS, although this presentation is more typical of SP-B and ABCA3 biallelic mutations. 2 The typical presentation of SP-C defects consists of dyspnea, cough or wheezing with an onset between 2 and 12 months of age, gradual cyanosis and failure to thrive.…”
Section: Polarized Light Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients with type I homozygous ABCA3 mutations such as W1142X/W1142X or type I/type II compound heterozygous ABCA3 mutations such as L982P/G1221S die of surfactant deficiency within the neonatal period (27). On the other hand, patients with the common missense mutation E292V and a second, specific mutation such as E690K or T1114M develop pediatric interstitial lung disease (pILD), the phenotype of which is milder than that of fatal surfactant deficiency, suggesting that the E292V ABCA3 mutation is responsible for the development of pILD (4). However, the mechanism underlying the phenotypic heterogeneity of lung disease associated with ABCA3 mutation remains unknown.…”
mentioning
confidence: 99%
“…Electron micrograph images revealed abnormally small and dense lamellar bodies and peripheral inclusions in this organelle. More recently [10], it has been shown that mutations in ABCA3 are not always associated with fatal neonatal surfactant deficiency, but can be the cause of other nonlethal lung diseases.…”
Section: Abca3mentioning
confidence: 99%